Radiation disease of the urinary tract: histological features of 18 cases. Issue 3 (March 1993) - Suresh, U R; Smith, V J; Lupton, E W; Haboubi, N Y
Abstract : AIMS: To study the spectrum of histological changes in the urinary tract caused by pelvic irradiation. METHODS: Biopsy specimens of ureter and bladder and cystectomy specimens from 18 patients who had received pelvic irradiation were studied and the histological features were arbitrarily grouped into early and late changes. RESULTS: A wide range of histological changes were noted of which submucosal inflammation, fibrosis, and epithelial damage were the commonest. Other less common features were interstitial haemorrhage, ureteritis and cystitis cystica, squamous metaplasia of vaginal type and perineural inflammation. CONCLUSIONS: Although epithelial changes were most prominent in early cases and stromal changes in the late cases, there was a continuing spectrum of epithelial damage which persisted many years after initial radiation. Similarly, submucosal fibrosis was equally prominent in early and late phases.